A Spectrum Analyzer in the 470 to 698 MHz Band Using Software Defined Radio for the Analysis of Digital Terrestrial Television Signals (DTTs) - Karla Andrade; Fausto Patiño; Tarquino Sánchez-Almeida (Engineering Proceedings, 2023)
This article presents the development of a prototype software for a terrestrial digital TV signal spectrum analyzer using software-defined radio (SDR). This study involves four phases: signal reception from Quito’s TV channels, configuring the software and hardware to work within the 470–698 MHz frequency range using the One-seg service of the ISDB-Tb standard, setting up the spectrum analyzer with a low-pass filter to reduce noise, and analyzing the results by visualizing digital TV signals from various areas of Quito with the SMPlayer software. While capturing TDT signals in Ecuador, it was discovered that some channels’ signals lacked playable audiovisual content on video players during testing.